Meta-Analysis and Evaluation by Insect-Mediated Baiting Reveal Different Patterns of Hypocrealean Entomopathogenic Fungi in the Soils From Two Regions of China - Masoudi, Abolfazl; Wang, Min; Zhang, Xiaoli; Wang, Can; Qiu, Zhaoxi; Wang, Wenying; Wang, Hui; Liu, Jingze (Frontiers in Microbiology, 2020)
A survey was carried out on forest soils and grassland soils from Hebei and Sichuan Provinces using Tenebrio molitor larvae as a bait and high-throughput DNA sequencing (HTS) of the fungal ITS2 ribosomal DNA was used to monitor the natural distribution of 3 leading hypocrealean families of insect fungal pathogens (Clavicipitaceae, Cordycipitaceae and Ophiocordicipitaceae). The occurrence of insect fungal pathogens in soil samples from 98 different sites were compared. The use of insect bait indicated that entomopathogenic fungi of genus Metarhizium were predominant, followed by Beauveria and Isaria. Molecular characterization using the Mz_FG543 intergenic region revealed that the Metarhizium species pool was phylogenetically composed of 3 closely-related species as follows; M. pingshaense (n=74), M. robertsii (n=51), and M. brunneum (n=26), as well as 1 isolate which clustered with M. flavoviride. Nine potentially new phylogenetic species were delimited within the M. flavoviride species complex by sequencing of the 5ʹ-TEF locus. Beauveria (n=64) and Isaria (n=5) isolates were characterized via sequence analyses of the Bloc region. Intergenic spacer phylogeny of the Beauveria isolates assemblage revealed the phylogenetic species within the B. bassiana clade. Interestingly, individuals of M. pingshaense (n=18) and M. brunneum (n=12) exhibited the presence of both mating-types in Sichuan Province. Similarly, for the Beauveria isolates, reproductive mode assays demonstrated that all 4 B. bassiana Sub-clades possessed bipolar outcrossing mating systems. Of these, 19 isolates contained 2 mating-types, and the rest were fixed for single mating-types, revealing opportunities for intra-lineage heterothallic mating. HTS results showed a significantly higher occurrence of the Clavicipitaceae family and the Metarhizium genus in the soil samples. Venn diagram showed that M. anisopliae s.l., I. farinose and B. bassiana as frequently abundant fungal pathogen OTUs (core) across sampling sites, while baiting method showed that the genus of Isaria isolated locally. The Mantel test verified that community dissimilarity increased significantly with geographical distance, suggesting that geographical coordinates are possible factors influencing insect fungal pathogen community composition in the studied sites. This study is the first to highlight the usefulness of utilizing soil baiting and deep sequencing to investigate the population dynamics of entomopathogens in soil.